AN ERROR IN THE CZECH EDITION OF MASARYK-RADLOV CORRESPONDENCE - Мурал, Жозеф (Философский полилог, 2018)
In the Czech edition of T. G. Masaryk’s corre-spondence with E. L. Radlov published in 2015, the editors misidentify a book, referred to in the letters, and as a consequence chronologi-cally misplace one letter preserved without dating. They repeat and magnify) the error committed already by their Russian colleague E. F. Firsov in his book “Т. Г. Масарик и рос-сийская интеллектуальная среда” 2005). They all fail to take into account Masaryk’s translation of David Hume’s second “Enquiry” into German 1883), to which Radlov’s expres-sions such as “your Hume”, “Hume” and “your Hume translation” refer in the relevant letters. Instead, the editors assert that Radlov first ex-pects and then receives Masaryk’s Prague inau-gural lecture on Hume and the calculus of probabilities “Počet pravděpodobnosti a Hu-mova skepse”, 1883), and next expects Ma-saryk’s shortened and modified German version of it “Dav. Humes Skepsis und die Wahr-scheinlichkeitsrechnung”, 1884). This is rather significant also as an indication of the rather widespread ignorance of Masaryk’s translation of Hume which could have been, for a while, his internationally best known work) among the Czech Masaryk scholars: thus Jaroslav Opat the founding director of the new Masaryk In-stitute of the Czech Academy of Sciences) in his 470-pages-long monograph on Masaryk’s philosophy and politics in 1882–1893 first con-siders it Masaryk’s own work “Eine Unter-suchung über die Prinzipen der Moral von David Hume”, 1883) and then ignores it com-pletely.